Matrix Sequences of Tribonacci and Tribonacci-Lucas Numbers - Soykan, Yüksel (Communications in Mathematics and Applications, 2020)
In this paper, we define Tribonacci and Tribonacci-Lucas matrix sequences and investigate their properties.